2013
DOI: 10.1088/0957-4484/24/46/465102
|View full text |Cite
|
Sign up to set email alerts
|

Boron nitride nanotubes and primary human osteoblasts:in vitrocompatibility and biological interactions under low frequency ultrasound stimulation

Abstract: In this paper we investigated a novel and non-invasive approach for an endogenous osteoblast stimulation mediated by boron nitride nanotubes (BNNTs). Specifically, following the cellular uptake of the piezoelectric nanotubes, cultures of primary human osteoblasts (hOBs) were irradiated with low frequency ultrasound (US), as a simple method to apply a mechanical input to the cells loaded with BNNTs. This in vitro study was aimed at investigating the main interactions between hOBs and BNNTs and to study the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…In addition to the absence of relevant toxicity on the cells, TEM images confirmed the phagocytosis of the material inside the cell cytoplasm. These findings were further corroborated by a later study by the same group, 69 where BNNTs taken up by osteoblast cells were stimulated through low frequency ultrasounds. BNNTs with a length inferior to 500 nm were obtained through a milling and annealing method 70 and coated with poly-L-lysine in order to attain a stable suspension.…”
Section: Applications In Compositessupporting
confidence: 72%
“…In addition to the absence of relevant toxicity on the cells, TEM images confirmed the phagocytosis of the material inside the cell cytoplasm. These findings were further corroborated by a later study by the same group, 69 where BNNTs taken up by osteoblast cells were stimulated through low frequency ultrasounds. BNNTs with a length inferior to 500 nm were obtained through a milling and annealing method 70 and coated with poly-L-lysine in order to attain a stable suspension.…”
Section: Applications In Compositessupporting
confidence: 72%
“…The results of these studies demonstrated improved dispersion in water and the generation of composite nanomaterials with enhanced mechanical and thermal properties 40,41 . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Interestingly, BNNTs possess a unique capacity of generating electric fields under mechanical stimulation (piezoelectricity) 12 , and recent studies indicate that the piezoelectric response of BNNTs is higher than piezoelectric polymers such as PVDF [42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, C2C12 myoblasts treated with poly‐ l ‐lysine (PLL)‐coated BNNTs at doses of pharmaceutical relevance have been shown to be viable and to efficiently differentiate into myotubes on two‐dimensional (2D) tissue culture plastic and microgrooved hydrogels (Ciofani et al ., ; Ricotti et al ., ). Additionally, preliminary in vitro results obtained on cultures of osteoblasts and neuron‐like cells treated with BNNTs and low‐frequency US have demonstrated that this method could successfully foster their function and differentiation without exerting major cytotoxic effects (Danti et al ., ; Ciofani et al ., ).…”
mentioning
confidence: 97%
“…Aqueous BNNT dispersion to administer our cellular models was prepared according to a published procedure (Ciofani et al ., ). Briefly, we used multiwalled BNNTs supplied by the Australian National University of Canberra (Australia), with boron nitride > 97 wt%, residual metal catalysts (Fe and Cr) ~1.5 wt% and a mean aspect ratio < 10 (Danti et al ., ). PLL (MW = 70 000–150 000, Fluka, St. Louis, MO, USA) was used for water stabilisation of BNNTs via non‐covalent coating.…”
mentioning
confidence: 99%
See 1 more Smart Citation